Editorial:[Hot Topic: The Role of Radiopharmaceuticals in Drug Discovery and Development(Executive Editor: Kalevi Kairemo)] - Kairemo, Kalevi (Current Pharmaceutical Design, 2009)
Radionuclide imaging together with other non-invasive imaging techniques have found a prominent place in the whole drug discovery and development process. The application of imaging has the potential to alter the direction of the development process. The fundamental questions to address are when in the development timeline do you use these imaging techniques and what is the current utilization of these imaging technologies? Imaging in psychopharmacology and CNS disorders, plays a critical role in drug development, because often nonclinical models do not exist (Pauwels et al.) [1]. Structures to be imaged are often small, location has to be known very precisely to estimate function disturbances and macrodosimetry is therefore more accurate. This issue focuses more on the targets outside the brain, main focus is therefore in cancer drug and cardiovascular drug development. Dosimetric and pharmacokinetic aspects are more complex and therefore discussed thoroughly. In this issue, cardiovascular drug development has been reviewed by academic network with members from Europe, North America and Japan (Ukkonen et al.) [2]. In this field there is an emerging need to understand the effects of drugs. Radiolabelled compounds offer possibility to study noninvasively cardiac perfusion, oxygen consumption, oxidative and substrate metabolism, myocardial efficiency of work, neural actions and receptors. Radiopharmaceuticals provide invaluable tool to study different routes of administration. Most cardiovascular drugs are oral and cancer drugs systemic intravenous. Inhalation provides benefits over other routes of administration, e.g. avoidance of firstpass- metabolism, and convenience for patients in administrations without repeated injections. Drug development of inhaled substances is complicated and usually development times are longer than ordinary drug development. The dosage in inhaled drugs causes many uncertainties as reviewed by Jekunen [3].